18F‐labeled folic acid derivatives for imaging of the folate receptor via positron emission tomography1. (23rd September 2013) - Schieferstein, Hanno; Ross, Tobias L.; Atzrodt, Jens; Derdau, Volker
<x xml:space="preserve">Abstract</x> The folate receptor (FR) is already known as a proven target in diagnostics and therapy of cancer. Furthermore, the FR is involved in inflammatory and autoimmune diseases. The major advantage as a valuable target is its strongly limited expression in healthy tissues. Over the past two decades, several folic acid‐based radiopharmaceuticals addressing the FR have been developed, and some of them show great potential for applications in clinical routine. However, most of these radiofolates were developed for single photon emission computed tomography imaging, and only a few can be used for positron emission tomography (PET) imaging. The development of suitable 18F‐labeled derivatives for PET imaging of the FR has aroused great interest and recent studies revealed very promising candidates for further development and translation into human applications. In this review, we focus on the development of 18F‐labeled folic acid derivatives for PET imaging of the FR and discuss various radiochemical strategies and approaches towards 18F‐folates. Besides radiochemistry and 18F‐labeling, we briefly look into the crucial pharmacological parameters and the preclinical in vivo performance of those 18F‐folates. Copyright © 2013 John Wiley & Sons, Ltd.